2018
DOI: 10.1016/j.neuropharm.2018.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes of GABA immunoreactivity in cortico-thalamic networks of an absence seizure model

Abstract: Absence seizures (ASs) are associated with abnormalities in gamma-aminobutyric acid (GABA) neurotransmission in the thalamus and the cortex. In the present study, we used light microscopy GABA immunocytochemistry to quantify the GABA-immunoreactive (GABA-IR) neurons and neuropil in the thalamic ventral basal (VB) nucleus, the nucleus reticularis thalami (NRT), the dorsal lateral geniculate (dLGN), the primary motor cortex (M1) and perioral region of the somatosensory cortex (S1po) of genetic absence epilepsy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…However, the cellular migration of interneurons should be finished before the appearance of SWDs in GAERS (Wonders & Anderson, 2006), therefore suggesting that their increased density could rather participate, at least indirectly, in the initiation of SWD by promoting the pro-epileptogenic activities of high-frequency oscillations (Cardin et al 2009;Veit et al 2017). In this case, comorbidities associated with AE could partly result from the plasticity induced by seizure recurrence, as suggested recently (Bombardi et al 2018). If this hypothesis is confirmed in the clinic, it raises the need to detect and block absence seizures as soon as possible in patients.…”
Section: Potential Role Of Gabaergic Inhibition In Sensory Impairmentmentioning
confidence: 74%
See 3 more Smart Citations
“…However, the cellular migration of interneurons should be finished before the appearance of SWDs in GAERS (Wonders & Anderson, 2006), therefore suggesting that their increased density could rather participate, at least indirectly, in the initiation of SWD by promoting the pro-epileptogenic activities of high-frequency oscillations (Cardin et al 2009;Veit et al 2017). In this case, comorbidities associated with AE could partly result from the plasticity induced by seizure recurrence, as suggested recently (Bombardi et al 2018). If this hypothesis is confirmed in the clinic, it raises the need to detect and block absence seizures as soon as possible in patients.…”
Section: Potential Role Of Gabaergic Inhibition In Sensory Impairmentmentioning
confidence: 74%
“…Because PV+ and SOM+ interneurons are essential for sensory coding and gamma oscillation (Cardin et al 2009;Buzsáki & Wang, 2012;Veit et al 2017), an increased number of these interneurons could explain the augmented gamma power in GAERS that not only favours SWDs, but also may alter sensory coding. A recent study showed no difference in terms of GABA+ interneurons in the S1Bf of GAERS (Bombardi et al 2018). By contrast, another recent study showed an elevation of PV+ interneurons in the S1 cortex of GAERS that was not present in WAG/Rij (Papp et al 2018).…”
Section: Potential Role Of Gabaergic Inhibition In Sensory Impairmentmentioning
confidence: 85%
See 2 more Smart Citations
“…Taken together, these data suggest that Fangjing decoction can ameliorate FS-induced cerebral injury through inhibiting neuronal apoptosis and controlling the Akt/m-TOR signaling pathway. As with other forms of epilepsy, dysfunctions in the brain GABA system are thought to have a crucial role in the pathogenesis of seizures [ 31 ]. In particular, many studies in human cohorts affected by seizures have highlighted potential abnormalities related to various genes coding for proteins of the GABAergic system, including transporters, synthetizing enzymes, and subunits of both GABA A and GABA B receptor subtypes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%